1994
DOI: 10.1103/physrevlett.72.3355
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of the inhomogeneous energy-density driven instability

Abstract: A category of oscillation identified with the inhomogeneous energy-density driven instability has been experimentally verified. This mode exploits the free energy available from shear in the Ex B Aow velocity. This shear is produced experimentally by applying different voltages to a segmented disk electrode located on axis at the end of a Q machine plasma column. As plasma conditions are varied between the two parameter regimes that, according to theory, correspond to the current-driven and shear-driven waves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…The instabilities could be the collisional drift wave instability, centrifugal instability, Kelvin-Helmholz instability, and inhomogeneous energy-density driven instability (IEED) $ [6,13]$ . In the present case, in which $(\kappa^{2}+k^{2})\gg(\Omega_{e}/\nu_{e})(r_{d}\Omega_{i}/C_{s})$ is satisfied, the drift wave instability is dominant, which is destabilized by collisions.…”
mentioning
confidence: 99%
“…The instabilities could be the collisional drift wave instability, centrifugal instability, Kelvin-Helmholz instability, and inhomogeneous energy-density driven instability (IEED) $ [6,13]$ . In the present case, in which $(\kappa^{2}+k^{2})\gg(\Omega_{e}/\nu_{e})(r_{d}\Omega_{i}/C_{s})$ is satisfied, the drift wave instability is dominant, which is destabilized by collisions.…”
mentioning
confidence: 99%
“…Furthermore, in the theoretical studies of Ganguli and Palmadesso (1988), Ganguli et al (1994), and Gavrishchaka et al (1996), it was shown that by changing the resonance properties of the system a combination of transverse localized electric fields and fieldaligned currents results in a lower excitation threshold current for CDEIC waves than inferred from the classical theory of the CDEIC instability. This theoretical prediction was validated in a number of laboratory experiments (Koepke and Amatucci, 1992;Amatucci et al, 1994;Koepke et al, 1994). It was also corroborated experimentally that broadband waves in the ion-cyclotron frequency range can be driven solely by a transverse, localized electric field, without the dissipation of a field-aligned current (Amatucci et al, 1998).…”
Section: Introductionmentioning
confidence: 51%
“…In recent experiments on Inhomogeneous Energy-Density Driven (IEDD) waves (Ganguli et al, 1985;Koepke et al, 1994;Amatucci et al, 1996;, quantitative comparisons with theoretical predictions were obtained (Koepke et al, 1995;1998a;Amatucci et al, 1998;Carroll et al, 1998;Peñano et al, 1998). Beyond verifying the existence of the excitation mechanism, Correspondence to: M. E. Koepke (mkoepke@wvu.edu) these comparisons reinforced detailed aspects of the theoretical model and also stimulated refinements and an expanded awareness of the details of the model.…”
Section: Introductionmentioning
confidence: 86%